Impact of Climate Changes on the Regional Energy Balances and Energy Exports from Russia - Klimenko, V. V.; Klimenko, A. V.; Tereshin, A. G.; Mitrova, T. A. (Thermal engineering, 2019)
Based on the approaches developed by the National Research University Moscow Power Engineering Institute (NRU MPEI) and the Energy Research Institute (ERI), the results of calculations of total world energy consumption and by groups of countries for the period up to 2050, with allowance for the anticipated climate changes, as well as resource and environmental restrictions, are presented. The estimates of energy consumption in various world regions for the period up to 2050 are based on a historical extrapolation approach to the research of energy consumption dynamics with allowance for the dependence of its optimal level on natural and geographical conditions. Using the SCANER simulation computer system developed by the Energy Research Institute for the study of energy markets, forecast fuel and energy balances for various regions have been made, which are aimed at meeting the national commitments on the Paris Agreement (2015) of the countries participating in the UN Framework Convention on Climate Change (UNFCCC), and international flows of the main energy carriers have been calculated. Estimates of the possible oil and gas export from Russia in the context of various scenarios for the development of the world energy sector have been made. It is shown that the fundamental processes currently taking place in the global energy complex, such as the development of new renewable and nonrenewable energy sources, the control and constraint on greenhouse gas emissions, and the uncertain status of nuclear energy, will contribute to an increase in demand for oil and, especially, natural gas from Russia and facilitate the rise in exports of these energy carriers, predominantly in the Asian direction.